2020
DOI: 10.1007/s10734-020-00569-4
|View full text |Cite
|
Sign up to set email alerts
|

Telework in academia: associations with health and well-being among staff

Abstract: As the development of technical aids for telework has progressed, work has become more flexible in time and space. Among academics, the opportunity to telework has been embraced by most, but it is unclear how it relates to their health and well-being. The aim of this study was to determine how frequency and amount of telework is associated with perceived health, stress, recuperation, work-life balance, and intrinsic work motivation among teaching and research academics. An electronic questionnaire was sent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 45 publications
7
58
0
3
Order By: Relevance
“…In a previous questionnaire study [15], respondents were asked about interest in participating in the present study. In total, 111 employees from six universities in different parts of Sweden reported their interest, and were contacted via e-mail.…”
Section: Study Samplementioning
confidence: 99%
See 2 more Smart Citations
“…In a previous questionnaire study [15], respondents were asked about interest in participating in the present study. In total, 111 employees from six universities in different parts of Sweden reported their interest, and were contacted via e-mail.…”
Section: Study Samplementioning
confidence: 99%
“…On the one hand, telework is found to increase individual autonomy, work/life balance, work control and productivity and reduce work related stress [1,2,5,[7][8][9]. On the other hand, telework is associated with increased stress, low boundary control (i.e., difficulty separating work and life domains), overtime work, lack of work motivation, and insufficient time for recovery [5,8,[10][11][12][13][14][15]. Thus, research shows disparate results with respect to the effect of telework on staff health and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reinforced how these detrimental changes could have an impact on non-workday sedentary behavior, poorer sleep quality, an increase in negative mood disorder, reduced perceptions of quality of life, and a considerable decrease in work-related health (Barone Gibbs et al, 2021). Another recent study conducted with higher education scholars revealed that the levels of stress were higher among those who worked remotely several times per week than those working remotely once per month (Heiden et al, 2021). In fact, other empirical studies have suggested that when people combine both daily job demands and daily home demands during remote work, they may experience increased emotional exhaustion (Abdel Hadi et al, 2021).…”
Section: The New (Ab)normal Context -Implications For Home and Work Lifementioning
confidence: 99%
“…In general, despite the advantages of telecommuting, a number of its disadvantages can be noted as social, for example, such as the absence of the usual offline communication, lack of feedback from colleagues; not being involved in the corporate culture of the company [16]; and organizational, for example, difficulties in self-organization during the working day [17,18]; and health problems [19,20].…”
Section: Distance Learning During the Global Challengementioning
confidence: 99%